Challenges and Opportunities in Implementing Disability Rights: Policy Evaluation and Access To Welfare For Persons With Disabilities - Mulyawan, Agus (International Journal of Law and Society, 2025)
Persons with disabilities represent a diverse segment of society, facing unique challenges in accessing public services such as education, healthcare, and employment. In response, Indonesia ratified the Convention on the Rights of Persons with Disabilities (CRPD) through Law No. 19 of 2011, which serves to promote, protect, and ensure equal rights and fundamental freedoms for individuals with disabilities. This commitment led to the enactment of Law No. 8 of 2016, replacing an earlier, more compassionate framework with one emphasizing equality and the protection of rights for persons with disabilities. The law defines individuals with disabilities as those facing long-term physical, intellectual, mental, or sensory limitations and emphasizes the necessity of special protections to uphold their rights and prevent discrimination. The method used in this study is a normative legal research method. This study evaluates the effectiveness of disability rights protection policies in Indonesia, revealing significant challenges despite the legal framework established by Law No. 19 of 2011. Access to education, healthcare, and employment remains limited due to inadequate facilities, discriminatory practices, and social stigma. Effective solutions require strengthening the legal framework, increasing awareness, and involving the disability community in policy planning. Furthermore, robust monitoring and enforcement mechanisms are essential for safeguarding rights. To enhance protections, improved coordination among ministries, ongoing training for service providers, inclusive education practices, and recognition of employers who hire individuals with disabilities are critical. These measures are vital for fostering a more equitable society and ensuring the rights of persons with disabilities are upheld sustainably.